Effectiveness of Business Licensing Laws for Micro, Small, and Medium Food Stalls in Mojosongo Urban Village - Vanya Lakhsitta Az Zahra; Nunik Nurhayati (Proceeding International Conference Restructuring and Transforming Law, 2025)
Micro, Small and Medium Enterprises (MSMEs) is a business sector that has a strategic role in the Indonesian economy. This research aims to find out: 1) Overview of MSME Business Licensing in Food Stalls in Mojosongo Urban Village, and 2) Legal Effectiveness of Risk-Based Business Licensing of Food Stalls in Mojosongo Urban Village. This research uses a juridical-empirical approach by combining analysis of legal regulations and direct interviews with MSME actors in Mojosongo Urabn Village. This research uses Lawrence M. Friedman’s theory of legal effectiveness to analyze the effectiveness of risk-based licensing laws specifically on Micro, Small and Medium Enterprises food stall, which have not previously been the focus of research in the context of the Mojosongo Urban Village area. The results show that Micro, Small and Medium Enterprises food stall in Mojosongo still face administrative constraints, lack of understanding of new regulations, and suboptimal institutional support. The legal effectiveness of risk-based licensing in this area is hampered by structural factors and a community legal culture that is not yet conducive. Risk-based licensing for Micro, Small and Medium Enterprises food stall in Mojosongo has not been fully effective. Increased socialization, simplification of administrative procedures, and strengthening the role of government in supporting Micro, Small and Medium Enterprise actors to achieve legal compliance are needed.